VECTOR ANOMALIES OF THE GEOMAGNETIC FIELD AROUND THE KERGUELEN PLATEAU - ノギ, ヨシフミ; セアマ, ノブカズ; イセザキ, ノブヒロ; ハヤシ, タモツ; カミヌマ, カツタダ; NOGI, Yoshifumi; SEAMA, Nobukazu; ISEZAKI, Nobuhiro; HAYASHI, Tamotsu; KAMINUMA, Katsutada (National Institute of Polar Research, 1991)
P(論文) The directions of two-dimensional magnetic structures around the Kerguelen Plateau were determined by using vector anomalies of the geomagnetic field obtained during the 30th and 31st Japanese Antarctic Research Expeditions. N-S and E-W directions of magnetic structure are deduced in the basin to the east (around 60°S, 88-91°E) and over (around 60°S, 71-88°E) the Kerguelen Plateau. Topographic and structural lineaments bring about N-S and E-W directions of magnetic anomaly lineations over the Kerguelen Plateau. In farther east (around 59°S, east from 91°E), stable NW-SE directions are obtained. The obtained stable NW-SE directions are in good agreement with the already identified geomagnetic anomaly lineations originated from the Southeast Indian Ridge (WEISSEL and HAYES : Antarct. Res. Ser., Vol. 19,Am. Geophys. Union, 165,1972). Stable NE-SW directions in the west (58-61°S, 62-68°E) of the Kerguelen Plateau were newly found in this expedition. Because sea bottom topography and free-air gravity anomalies show no structural offset, stable NE-SW directions are due to the geomagnetic anomaly lineations produced by polarity reversals. NE-SW directions obtained from vector anomalies of the geomagnetic field support presumptive directions of the geomagnetic anomaly lineations originated from an ancient abandoned ridge, that is, the mid-ocean ridge between India and Antarctica from Late Jurassic (160Ma) to Middle Cretaceous (96Ma) (POWELL et al. : Tectonophysics, 155,261,1988). These results may provide detailed kinematics of the growth of the Indian Ocean. departmental bulletin paper